(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Our reflection is based on Mallarmé’s Throw of Dice (Un Coup de dés, 1897) 1 considered as an inaugural gesture that is at the origin of several developments later artistic or poetic works. She tries to understand the consequences of this gesture of non-exhaustive, but constellar way, as a paradigmatic reference of manifestations artistic forms that we consider representative, such as Brazilian concrete poetry and its subsequent developments. In France we privilege the heritage of gesture not in poetry, but in the plastic arts through the example of Marcel Duchamp. We will try, from of these two artists, show that the gesture is at the same time a figure of criticism and corresponds to a “vital trait”.